American public finance - Shultz, William J.; Harriss, C. Lowell (Englewood Cliffs, N.J., Prentice-Hall, 1965)
This edition is designed to provide the necessary understanding of, more accurately, to build a basic foundation, for dealing with the problems of public finance. It presents only a broad survey - but a balanced, penetrating one - of American fiscal structure and theory.
First published in 1931 under title: American public finance and taxation.
Includes bibliographical references and index.
oif 01/02/2019
Loans
Keywords: Finance, Public; Taxation